A TEORIA DAS OPÇÕES REAIS COMO INSTRUMENTO DE AVALIAÇÃO NA ANÁLISE DE UM PROCESSO DE FUSÃO / INCORPORAÇÃO DE EMPRESAS - Santos, David Ferreira Lopes (2004)
The main objective of this paper it is to use the Real Options Theory (ROT) in the process of fusion / incorporation of companies. The work was developed in small and middle size companies in the petroleum chain, specifically in the city of Macaé/RJ, trying to measure the real efficacy of the proposal theory at these investments. The motivation for the work resides in the need that such companies have to compete in a market that is becoming everyday more competitive, where the strategy of incorporation and fusion do not exist in the culture of these businessmen, but it s, as a matter of fact and an important alternative for the sustainability of the business. Taking in consideration the shortage of investment funds in this country and all others related structural problems that makes more difficult to the Brazilian companies to compete in the global economy, imprecise decisions in where to allocate the funds may bring irreversible damages, and so, the tools used for making decisions are becoming more important every day. To evaluate the efficacy of the theory, this work presents the theoretical reference that sustains the ROT, the process of fusion/incorporation and it s implication and finally a study of a case that bears the problem, validating the hypothesis and giving proof of the efficacy of the tool when compared to the main methodology used for: the Discounted Cash Flow.